2015
DOI: 10.1007/s40618-014-0235-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium–phosphate metabolism in patients with multiple sclerosis

Abstract: Introduction and objectivesThe purpose of this study was to evaluate the concentration of 25-hydroxycholecalciferol and parameters of calcium–phosphate metabolism at different periods of relapsing–remitting multiple sclerosis (RRMS).Materials and methodsForty-five patients, residents of Poland (49°–50°, N), were enrolled in the study, i.e. 15 immediately after the diagnosis of RRMS, 15 at the early stage and 15 at the advanced stage of RRMS. The results were compared to values obtained in 20 age- and sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…In turn, the determination of levels of albumins and total protein which has an impact on the active fraction of total calcium could have modified the results. The lack of differences in the levels of ALP between VitDd, VitDi, and VitDn is consistent with the study conducted in patients who did not use DMT [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…In turn, the determination of levels of albumins and total protein which has an impact on the active fraction of total calcium could have modified the results. The lack of differences in the levels of ALP between VitDd, VitDi, and VitDn is consistent with the study conducted in patients who did not use DMT [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…24 According to Kubicka-Baczyk et al, the MS patients had a significantly higher level of serum parathormone than the controls. 25 In their study, daily urine calcium excretion was lower in the patients than in the healthy controls; the serum phosphorus, calcium and alkaline phosphatase levels were higher in the patients than in the controls, but these differences were not statistically significant. 25 In contrast to all the aforementioned studies, Chałas found that the calcium levels in the saliva of the MS patients were significantly lower than in the healthy controls.…”
Section: Discussionmentioning
confidence: 83%
“…25 In their study, daily urine calcium excretion was lower in the patients than in the healthy controls; the serum phosphorus, calcium and alkaline phosphatase levels were higher in the patients than in the controls, but these differences were not statistically significant. 25 In contrast to all the aforementioned studies, Chałas found that the calcium levels in the saliva of the MS patients were significantly lower than in the healthy controls. 3 This difference may be related to different patient characteristics, such as the duration of the disease, the type of medications taken, study sample size, the methods of calcium detection, and different inclusion and exclusion criteria according to the study design.…”
Section: Discussionmentioning
confidence: 83%
“…Metastatic calcinosis cutis is a rare but potentially devastating consequence of hypercalcaemia. On the other hand, in patients suffering from multiple sclerosis (MS), low calcium and vitamin D levels have been shown to correlate with MS relapses, decreased anti-inflammatory effects and immunomodulation 1–4. It is thus common practice among neurologists to recommend additional sources of vitamin D and calcium for this population 5 6.…”
Section: Introductionmentioning
confidence: 99%